Treatment of intrauterine infection of viral and bacterial etiology in newborns with drugs of recombinant interferon alfa-2b in the Republic of Kyrgyzstan - E. M. Alymkulova; A. T. Romanova; S. T. Abduvalieva; N. F. Gagloeva; T. P. Guseva (Лечащий Врач)
In an open observational prospective comparative study based on the National Center for Maternal and Child Health (Department of Pathology of Newborns and Premature Infants) Kyrgyzstan included 103 newborn children with a confirmed diagnosis of intrauterine infections of various etiologies, randomized into two groups: the main group – 54 children receiving standard therapy (antibacterial, antifungal, symptomatic) in combination with interferon alpha-2b with antioxidants in the dosage form of rectal suppositories (150,000 IU); the comparison group consisted of 49 newborns who received only standard therapy. There was a significant improvement in the general condition of children, which was assessed based on the positive dynamics of the main clinical symptoms of the disease against the background of interferon therapy compared with the comparison group, as well as an increase in the physical development of newborns. Statistically significant positive dynamics of laboratory parameters in the main group compared with the comparison group was determined: a decrease in leukocytosis, neutrophil intoxication index, procalcitonin and lactate levels, leukocyturia and bacteriuria (p < 0.05). There was an increase in the level of serum IFN, the ability of cells to produce both IFN-α and IFN-γ by immunocompetent cells, an increase in the phagocytic function of neutrophils (an increase in phagocytosis from 42% to 51%, phagocytic index from 2.1 ± 0.1 to 3.4 ± 0.2, absolute phagocytic index from 5462 ± 1136 to 10845 ± 1127, a decrease in percent of immature forms of neutrophils from 17.5 ± 2.3 to 7.8 ± 1.2). The use of drugs of recombinant interferon alfa-2b in the early neonatal period led to normalization of the number of lymphocytes, the number of activated cytotoxic T-lymphocytes (5.7 ± 0.9), normalization of immunoglobulin indices of the main classes. No deaths have been recorded. The complete absence of adverse events during the research period and unmotivated refusals of mothers from therapy proved the high tolerability and safety of this drug. The results obtained make it possible to recommend the inclusion of IFN-a2b preparations with antioxidants (rectal suppositories 150,000 IU) in standard treatment regimens for intrauterine infections in full-term and premature infants.